Designing a Learning Trajectory Using the Rangguk Dance Context for Reflection Material - Army Ramadhany; Ester Sianturi; Arina Amelia; Karolina Puja; Bagas Praharesa; Tria Gustiningsi (Jurnal Inovasi Matematika, 2026)
This study aims to produce a learning trajectory on the topic of reflection using the context of Rangguk dance. The background of this study is that students still experience difficulties in understanding transformation geometry, particularly the concept of reflection. These difficulties are evident in their understanding of basic concepts, their ability to visualize the image of an object after reflection, and their ability to relate the concept to its applications. This condition indicates the need for a learning approach that can help students understand the concept of reflection more meaningfully. The research employed is design research with a validation studies type, which consists of three stages: preliminary design, design experiment, and retrospective analysis. The research subjects involved in this study were ninth-grade junior high school students. Data were collected through tests, interviews, observations, and documentation, and analyzed using data triangulation. This study produce learning trajectory consists of six activities Activity 1: Observing a video of Rangguk dance; Activity 2: Drawing sketches of the dancers’ hand movements from the video; Activity 3: Representing the dancers’ hand movements on floor tiles based on the sketches; Activity 4: Depicting the dancers’ hand movements on the Cartesian coordinate plane and answering several questions; Activity 5: Reconstructing the movements using GeoGebra; Activity 6: Concluding and formulating the definition. The results indicate that this learning trajectory helps students gradually understand the concept of reflection, moving from concrete representations to formal understanding.